Communication and service quality as drivers of public satisfaction in Bojonegoro - Choirul Saleh; Ferdhianzah, Hefry Johan; Trilaksono, Hendrik (Jurnal Studi Komunikasi, 2026)
This study examines the influence of communication quality and service quality on public satisfaction within a local government education service context. Although efforts to improve transparency and communication have increased, public satisfaction outcomes remain inconsistent, raising questions about whether communication directly drives satisfaction or depends on service performance. Using a quantitative explanatory design, data were collected from 385 public service users and analysed using PLS-SEM. The study tested three hypotheses: the direct effects of communication quality and service quality on public satisfaction, and the moderating role of service quality in the communication–satisfaction relationship. The results indicate that service quality has a strong and significant positive effect on public satisfaction, confirming its central role in shaping citizens’ service evaluations. In contrast, communication quality does not show a significant direct effect on satisfaction. This finding reflects a bureaucratic service environment in which citizens prioritise tangible service outcomes over communicative aspects. Furthermore, service quality significantly moderates the relationship between communication quality and public satisfaction, suggesting that communication becomes meaningful only when supported by reliable service delivery. These findings reveal a service–communication paradox and contribute to public service theory by demonstrating that communication effectiveness is contingent upon service performance.